Regulation of Securities Offering Through Equity Crowdfunding: A Juridical Comparison Between Indonesia and Singapore - Zalfa Fattaya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The purpose of this study is to examine and analyze the legal framework governing the offering of securities through equity crowdfunding in Indonesia and Singapore, as well as to identify the similarities and differences between the two regulatory regimes. This research employs a normative legal research method, which focuses on the study of applicable positive legal norms and relevant legal doctrines. This method was chosen because the research centers on the analysis of legislation and legal concepts governing securities offerings through equity crowdfunding, as well as investor protection mechanisms in the legal systems of Indonesia and Singapore.The results of this study show that, in comparing the regulatory frameworks, although both countries share the same objective of balancing innovation and market protection, they differ significantly in their approaches. Singapore adopts a principle-based approach emphasizing intermediary integrity, whereby platform operators are required to meet the high standards of the Capital Markets Services (CMS) Licence and apply investor segmentation (Accredited vs. Retail) to tailor protection. In contrast, Indonesia implements a rules-based approach that prioritizes inclusiveness, imposing specific limitations on issuer profiles (non-conglomerate MSMEs) and applying direct interventions to mitigate risks for retail investors through investment caps based on a percentage of income.